2013
DOI: 10.1021/cs400683e
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Oxide on Fe2O3 Core–Shell Catalysts: Probing the Nature of the Structural Motifs Responsible for Methanol Oxidation Catalysis

Abstract: A series of MoO x -modified Fe 2 O 3 catalysts have been prepared in an attempt to make core−shell oxidic materials of the type MoO x /Fe 2 O 3 . It is conclusively shown that for three monolayers of Mo dosed, the Mo stays in the surface region, even after annealing to high temperature. It is only when the material is annealed above 400 °C that it reacts with the iron oxide. We show by a combination of methods, and especially by XAFS, that at temperatures above 400 °C, most of the Mo converts to Fe 2 (MoO 4 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
105
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 32 publications
9
105
0
Order By: Relevance
“…This confirms that VO x is present in the surface layers. CO production is observed at higher temperatures, reaching its peak at approximately 230 °C; similar behaviour was observed for previous Mobased systems, though formaldehyde production peaks at higher temperatures for MoO x /Fe 2 O 3 [18,19]. It is suggested that isolated cation sites are responsible for CO generation [18,20,24,25]; surface VO x is present in sufficient quantity to preclude multiple neighbouring Fe sites ( : this can be ascribed to the shell-core process, which is known to enhance surface area [18,19].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…This confirms that VO x is present in the surface layers. CO production is observed at higher temperatures, reaching its peak at approximately 230 °C; similar behaviour was observed for previous Mobased systems, though formaldehyde production peaks at higher temperatures for MoO x /Fe 2 O 3 [18,19]. It is suggested that isolated cation sites are responsible for CO generation [18,20,24,25]; surface VO x is present in sufficient quantity to preclude multiple neighbouring Fe sites ( : this can be ascribed to the shell-core process, which is known to enhance surface area [18,19].…”
Section: Resultssupporting
confidence: 86%
“…This behaviour has similarities to that seen for Mo-based shell-core catalysts reported previously. However, 3 ML VO x /Fe 2 O 3 is a poorer catalyst than 3 ML MoO x /Fe 2 O 3 , achieving only 55% selectivity to formaldehyde at 50% conversion compared to 89% selectivity at 50% conversion for MoO x /Fe 2 O 3 [18]. Similar catalytic behaviour is observed upon repeated usage, although studies of prolonged usage and catalyst longevity have yet to be performed.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Nanostructured iron molybdenum alloys and their oxides exhibit desirable chemical, electrical, and mechanical properties showing promise for applications in gas sensing [1][2][3][4], energy storage [5][6][7], and catalysis [8][9][10][11][12]. Of particular interest, are Fe-Mo nanoalloys used for catalytic chemical vapor deposition of carbon nanotubes (CNTs).…”
Section: Introductionmentioning
confidence: 99%